2019
DOI: 10.3390/su11102809
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Wind Turbine Operation by Artificial Neural Network-Based Active Gurney Flap Flow Control

Abstract: Flow control devices have been introduced in the wind energy sector to improve the aerodynamic behavior of the wind turbine blades (WTBs). Among these flow control devices, Gurney flaps (GFs) have been the focus of innovative research, due to their good characteristics which enhance the lift force that causes the rotation of the wind turbine rotor. The lift force increment introduced by GFs depends on the physical characteristics of the device and the angle of attack (AoA) of the incoming wind. Hence, despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…The use of real wind speed data in the FAST simulation environment is important since it allows a detailed analysis of the performance of the designed control strategy in a realistic scenario. In fact, the data collected from this meteorological station have been used in several publications …”
Section: Design Of the Proposed Yaw Control Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The use of real wind speed data in the FAST simulation environment is important since it allows a detailed analysis of the performance of the designed control strategy in a realistic scenario. In fact, the data collected from this meteorological station have been used in several publications …”
Section: Design Of the Proposed Yaw Control Strategymentioning
confidence: 99%
“…In fact, the data collected from this meteorological station have been used in several publications. 40,41 A detailed analysis of the available wind data has been conducted, and six different cases with a variety of stable wind conditions have been identified and isolated to be used in the study of the performance of the proposed yaw control system. One example case where the wind conditions remain rather stable during a time span of 10 000 s is represented in Figure 11.…”
Section: Design Of the Proposed Yaw Control Strategymentioning
confidence: 99%
“…that modify the exterior geometry of the body as a function of time. For instance, piezoelectric bending actuators have been used to drive flaps to manipulate the flow at the back of a nominally two-dimensional blunt trailing edge [52] and active Gurney flaps have been used to control the aerodynamic characteristics of wind turbine blades [53]. In these examples, dynamic shape modification is enabled via servo-mechanisms or microelectromechanical systems to actively control the exterior flow.…”
Section: Afc Local Actuatorsmentioning
confidence: 99%
“…After conducting few tests, he found out that this simple modification allowed approaching turns with higher velocity and also increasing the car speed on straight lines. The simple construction of this device has encouraged researchers to investigate its application in different areas [7][8][9][10], and especially in wind turbines, where they do represent one of the most interesting solutions [11,12]. It has been found that the effect of the lift coefficient enhancement of the GF is connected with the change of the flow structure at the trailing edge, as it is shown in Figure 1, which reports the vorticity contours near the trailing edge of the airfoil.…”
Section: Introductionmentioning
confidence: 99%